Large-scale pseudotachylytes and fluidized cataclasites from an ancient subduction thrust fault - Christen, D. Rowe; Casey Moore, J.; Alexander, W. McKeirnan; MENEGHINI, FRANCESCA (Geology, 2005)
In the Kodiak accretionary complex, Kodiak Island, Alaska, pseudotachylyte occurs in black, locally vitreous ultrafine-grained fault rock. Microscopic observations show that the pseudotachylytes are composed of glass, with vesicles, amygdules, microlites, and flow structures, indicating a frictional melt. The pseudotachylyte is gradational to cataclasite and shows outcrop-scale injection and ductile deformation structures. The cataclasite was ductily mobile (i.e., fluidized) simultaneous with the formation and emplacement of pseudotachylyte melt. The pseudotachylytic rocks postdate the stratal disruption fabric of associated shear-zone melanges and show similar direction of thrust transport, and have undergone limited subsequent deformation. We interpret the stratal disruption as resulting from underthrusting of the subducting plate and pseudotachylyte development as the final activity of this thrust surface. The gradational contacts between pseudotachylyte and cataclasite demonstrate that the cataclasite also formed as a seismic product and may represent paleoseismic rupture zones, possibly of very great earthquakes, with or without accompanying pseudotachylytes. The pseudotachylytes are voluminous, and many are spatially disconnected from generation surfaces. This style is distinct from pseudotachylytes described in other environments, and this may explain the rarity of documented examples of subduction-thrust pseudotachylyte.